Protestantism in contemporary China - Hunter, Alan (Cambridge studies in ideology and religion, 1993)
This study investigates the historical and political conditions which have contributed to the state of the Protestant community in China, and the kinds of spirituality and religious life that it has evolved. The authors draw on extensive fieldwork, and offer fascinating insights into the beliefs and practices of a little-documented section of Chinese society. They show that healing, protection, and vengeance by gods have been deep-rooted elements of Chinese religiosity for several hundred years, notions appropriated by Christians who now emphasize the powers of Jesus. Chinese Protestantism is seen to result from an interesting blend of the old and the new, and comparative material is adduced which sets Protestantism side by side with Catholicism and Buddhism, the two religions in China of comparable scope. A wide range of sources are utilized by the authors, and these lead to one of the most complete and detailed surveys of Christianity in China ever produced.